Volume guarantee ventilation in premature neonates with respiratory distress: a comparative study - A., Sudheer K.; B., Sunil; Rajiv, P. K.; Kripail, Mathew; Nithya, E. (International Journal of Contemporary Pediatrics, 2019)
Background: Respiratory distress syndrome (RDS) occurs in about 50% of preterm infants born at less than 30 weeks of gestational age. Surfactant therapy and mechanical ventilation have been the standard of care in the management of RDS. Objective of this study to compare the time required to achieve successful extubation criteria in Volume guarantee mode of ventilation to that with Time cycled pressure-limited mode of ventilation and the duration of mechanical ventilation between them in preterm neonates ventilated for respiratory distress syndrome. Method: The study was done at Neonatal intensive care unit, Amrita Institute of Medical Sciences and Research Centre, Kochi, Kerala over a period of 2 years. Total of 37 inborn preterm neonates between 26 weeks to 32weeks with RDS requiring mechanical ventilation were included in 2-year study period with 18 babies in 1st year study period ventilated with SIPPV mode and 19 babies in 2nd year study period on SIPPV–VG mode of ventilation. Analysis was done using SPSS v. 16 software. Results: In the present study the neonates receiving SIPPV-VG ventilation had stable and equivalent gas exchange at significantly lower MAP and PIP compared to neonates receiving SIPPV -TCPL. Also, neonates receiving SIPPV-VG had achieved significantly faster extubation criteria than SIPPV-TCPL and hence lesser duration of ventilation. Conclusion: Our study concludes that Volume Guarantee ventilation achieves near stable tidal volume delivery by auto-weaning peak inspiratory pressures thereby promoting early extubation and hence reducing volutrauma and barotrauma in contrast to TCPL mode.